An Efficient Localization Method Based on Adaptive Optimal Sensor Placement. (26th August 2014) - Lee, Jin-Hee; Kim, Kyeongyul; Lee, Sang-Chul; Shin, Byeong-Seok
Abstract : We propose a ZigBee-based localization method that estimates the distance between ZigBee nodes employing the strength of wireless signal. It enables us to track the location of a user by means of trilateration, using the distance between fixed nodes deployed at predetermined locations and a mobile base station. In addition, we propose a method to determine the optimal placement of the fixed nodes using minimum Bayes error estimation based on Gaussian distributions. As a result, this method can accurately estimate the position of the mobile base station with a minimum number of fixed nodes.